Associations of Serum Calprotectin, Arterial Stiffness and Long COVID Symptoms in Dalmatian Kidney Transplant Recipients - Tina Đogaš; Ivana Novak; Marija Babić; Marijana Vučković; Leida Tandara; Josipa Radić (Viruses, 2023)
We aimed to explore long COVID symptoms, serum calprotectin levels, and the parameters of arterial stiffness in Dalmatian kidney transplant recipients (KTRs) and their possible associations. A cross-sectional, single-center case-control study on 98 KTRs who had recovered from COVID-19 was performed. Long COVID symptoms were explored via standardized questionnaires assessing quality of life, and serum calprotectin was also measured. Out of 98 KTRs with a mean age of 62 years, 63 (64.3%) were men. Medical history, clinical and laboratory parameters, and arterial stiffness measurements were obtained for each study participant. Difficulties with mobility were present in 44.3% of the KTRs, while difficulties with self-care were present in 6.2%, difficulties with usual activities were demonstrated by 35.1%, pain in the extremities was present in 52.5%, and anxiety and depression were present in 26.8%. Our results showed significant differences regarding serum calprotectin levels in clinical manifestations of acute COVID-19 and follow-up laboratory parameters. The most significant positive predictors of the serum calprotectin value in the KTRs were respiratory insufficiency, acute kidney failure, the prescription of antihypertensives, leukocyte and neutrophil counts, the neutrophil/lymphocyte ratio and lactate dehydrogenase levels. Negative predictors were the time since COVID-19, high-density lipoprotein levels, kidney function parameters, and the lymphocyte count. To conclude, serum calprotectin has emerged as a possible promising biomarker for subclinical allograft rejection; however, further studies are needed to better understand this subject.